Facile Preparation of an Effective Intumescent Flame Retardant Coating for Cotton Fabric. Issue 3 (14th May 2020) - Cheng, Xian-Wei; Wu, Yan-Xiang; Hu, Bi-Qing; Guan, Jin-Ping
Abstract : In the present study, phytic acid was used as an environmentally sustainable phosphorus-containing flame retardant (FR) to improve the flammability of cotton fabric. The facilely prepared approach is adequate to offer an intumescent FR system for cotton as phytic acid and triethanolamine could serve as the acid source and blowing agent and cellulose substrate may functional as a carbon source. The flame retardancy, thermal stability, heat and smoke generation and mechanical performance of cotton fabrics were evaluated. The cotton fabrics coated with phytic acid with 70 g/L at pH 5 had a weight gain of 15.1%, and self-extinguished via an intumescent charring mechanism in vertical burning test, and the textile structures of burned portion were well preserved. The intumescent FR coating also greatly reduced the heat and smoke generation ability of cotton, and enhanced its thermal stability at high temperature, but suffered from poor washing resistance. The present intumescent FR system based on phytic acid is an eco-friendly and sustainable production approach compared to the synthetically engineered chemicals.